Citra Perempuan dalam Novel Si Parasit Lajang Karya Ayu Utami: Kajian Kritik Sastra Feminisme dan Implementasinya Sebagai Bahan Ajar Bahasa Indonesia di SMA - Fadli, Wahyu Lailul, Prof. Dr. Ali Imran Al-Ma'ruf, M.Hum, Prof. Dr. Abdul Ngalim, M.M., M.Hum (2015)
This research has four goals. 1) To describe the sosiohistoris background of Ayu Utami as an author of "Si Parasit Lajang" novel. 2) To describe the structural study of "Si Parasit Lajang" novel by Ayu Utami. 3) To describe the image of women in ayu utami's novel "Si Parasit Lajang" based on literary criticism feminism. 4) To describe the implementation of women image in ayu utami's novel "Si Parasit Lajang" as Indonesian literature material in SMA.This type of research was qualitative descriptive. The object of this study is the image of women in the novel "Si Parasit Lajang". The subject of this research was "Si Parasit Lajang" novel by Ayu Utami. The data used in the form of words, phrases, clauses, sentences, or discourse that contains the image of women in the novel "Si Parasit Lajang". The data source of this research is the novel "Si Parasit Lajang" by Ayu Utami. The techniques of data collection in this study used a library technique and record. Triangulation that used in this research was data triangulation and triangulation theory. Structurally the theme of "Si Parasit Lajang" novel by Ayu Utami was about a woman who wanted the equality with men. The storyline that was used by Ayu Utami was chronological plot. In this novel, the key figures were "I". As the antagonist is Sahal. Meanwhile, which includes figures tritagonis is Gofur, Ming Dao, Mrs. cast of "I", Cynta, Erik, Orlow, Timun and Saepi. The scene background took a place in Jakarta, Tulungagung, Trenggalek, Europe dan Japan. The time background happened in 1990-2000. The social background was in military regime in the new era under the leadership of president Soeharto. The image of women in "Si Parasit Lajang" novel by Ayu Utami included three things. 1) Educated women. 2) Tenacious and independent women. 3) High social personality women. The implementation of novel research results "Si Parasit Lajang" by Ayu Utami as learning material at school can be viewed from three things. 1) The relevance to the aims of education. 2) The relevance to the content standards. 3) The relevance to learners.